Training Community Pharmacy Staff How to Help Manage Urgent Mental Health Crises - Nathaniel Rickles; Albert Wertheimer; Yifan Huang (MDPI AG, 2019)
Nearly 44 million Americans are affected by mental illness every year. Many individuals, however, are not diagnosed and/or do not receive treatment. The present manuscript reviews the incidence of mental illness, the continuum from mental wellness to mental illness, and the role of the pharmacy staff in helping individuals manage different mental health needs. In particular, there is discussion of stigma of mental illness that those with mental health needs experience by those around them including health professionals such as pharmacy staff. One way to resolve such stigma is through training such as Mental Health First Aid (MHFA). The paper reviews key aspects of MHFA, the evidence supporting MHFA, and how MHFA relates specifically to pharmacy practice and services. A conceptual framework for MHFA and its relationship to individual factors, attitudes, behaviors, and outcomes. Lastly, a discussion is presented that briefly compares MHFA to other similar approaches to helping those in mental health crises, the limits of what is known about MHFA, and what future research might explore to better understand the outcomes of pharmacy staff providing mental health education, support, and referral to care.